Training of Recycled Plastic Bags Crafting in Morokrembangan Village, Surabaya City: Pelatihan Pembuatan Kerajinan Tas Daur Ulang Plastik di Kelurahan Morokrembangan Kota Surabaya - Alifia Zahra Ramadhani; I Gusti Ayu Anjely; Thazkia Yaumil El Haq; Nurkholish Majid (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
This community service program aims to strengthen the environmentally based creative economy through the utilization of household waste in RW 05, Morokrembangan Village, Krembangan District, Surabaya City. The main focus of the program is the empowerment of Karang Taruna youth through training in producing recycled bags from sachet packaging, which had previously shown limited sustainability. The activities were carried out using a community-based participatory approach, including field observation, coordination with local stakeholders, collection of materials from the waste bank, and a workshop conducted with local artisans. The results indicate improved technical skills among participants, increased ecological awareness, and interest from several youths to further develop independent businesses. This program makes a tangible contribution by revitalizing a stagnant local potential while emphasizing the role of young people as agents of change in creativity-based waste management.